A Critical Analysis of Finite-Element Modeling Procedures for Radial Bearing Stiffness Estimation. (30th August 2021) - Gabrielli, Alberto; Battarra, Mattia; Mucchi, Emiliano
Abstract : Different strategies are commonly employed by researchers in order to decrease the computational effort associated with the finite-element analysis of rolling-element bearings. The purpose of this work is to review and analyze the procedures and hypotheses that may be exploited to evaluate the nonlinear radial stiffness of these components. Techniques are utilized to develop a meshing procedure aimed at balancing the computational effort and the accuracy of the results, to define a robust approach to the problem. The geometry is reduced by taking advantage of the available symmetry planes, by removing unloaded rollers, and by substituting the shaft with an equivalent sinusoidal load. In addition, the element dimensions are adapted to the applied load depending on the size of the contact area as computed by means of the Hertz theory. The proposed methodology may be applied to all bearing types provided that symmetry conditions and contact area dimensions are properly assessed. The estimated stiffness is compared against analytical formulae retrieved from the literature. Influence of different element types, roller position, cage, and clearance on accuracy and computational time is discussed.